PENGEMBANGAN KETERAMPILAN BERBICARA ANAK DIDIK BERBASIS METODE EKSTEMPORAN PADA MATA PELAJARAN BAHASA INDONESIA - Nainggolan, Rustani; Ningsih, Putri Amelia; Alamanda, Alfa (Educational Technology Journal, 2024)
Speaking skills at the secondary school level teach students how to speak in public. The first step that teachers need to do is to apply a variety of knowledge about speaking skills so that students really understand what they will convey to others. Students can present factual, factual, and communicative information to others if they have a holistic view, obtained from various sources. This study aims to provide an understanding of assessment of secondary school student's speaking skills. For speaking, pupils might employ four method. One of the most commonly used methods is the improvisation method. This extemporaneous method, only prepares an outline of the theme or material that will be delivered to the listener. Then the outlines, students develop their own with the intellectual abilities that students have. This extemporaneous method is very beneficial for the development of students' speaking skills. Language factors and non-language factors also greatly support the effectiveness of students in speaking. So that these factors must be considered by students when speaking in front of an audience. Keywords: extemporaneous method; speaking skills; knowledge; students.